PENERAPAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT KONSUMTIF PADA PT. ADIRA DINAMIKA MULTI FINANCE CABANG MAKASSAR - Fathiyah Thufailah Muhammad Nur; Ilham Abbas; Sahban (Qawanin Jurnal Ilmu Hukum, 2020)
. This study aims to realize the principle of prudence for prospective borrowers in order to minimize bad credit at PT. Adira Dinamika Multi Finance Makassar Branch and see the steps taken by PT. Adira Dinamika Multi Finance Makassar Branch has bad debts by debtors. This study uses empirical research methods. The research location was carried out at PT. Adira Dinamika Multi Finance Makassar branch. Types and sources of data used are primary data and secondary data. Data study techniques, library research (library research) and field research (field research). Data analysis, namely data obtained, either primary data or secondary data, will then be processed and analyzed to produce, then presented descriptively. The result of this research is PT. Adira Dinamika Multi Finance Makassar branch in applying the principle of prudence is to use a feasibility analysis, namely character, capacity, capital, collateral, and economic conditions (5C). Then the steps achieved by PT. Adira Dinamika Multi Finance Makassar branch in bad credit through rescheduling, reconditioning and collateral execution stages.